2015
DOI: 10.1167/15.11.10
|View full text |Cite
|
Sign up to set email alerts
|

Translation and articulation in biological motion perception

Abstract: Recent models of biological motion processing focus on the articulational aspect of human walking investigated by point-light figures walking in place. However, in real human walking, the change in the position of the limbs relative to each other (referred to as articulation) results in a change of body location in space over time (referred to as translation). In order to examine the role of this translational component on the perception of biological motion we designed three psychophysical experiments of faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 40 publications
1
32
2
Order By: Relevance
“…The point-light actions of walking, throwing, and kicking were presented in sagittal views, and the jumping jacks and elbow-to-knee were presented in frontal views, where larger point-light motions can be seen. The mean position of the pointlight dots in each frame was used as the spatial center of each image frame because the present study focused on the articulational aspect (positional changes in the body parts relative to each other) rather than the translational aspect (changes in the body location in space over time) of human movements (Masselink & Lappe, 2015). Scrambled biological motions were created by randomizing the starting positions of each point while keeping its motion path within the area covered by the Figure 1.…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
“…The point-light actions of walking, throwing, and kicking were presented in sagittal views, and the jumping jacks and elbow-to-knee were presented in frontal views, where larger point-light motions can be seen. The mean position of the pointlight dots in each frame was used as the spatial center of each image frame because the present study focused on the articulational aspect (positional changes in the body parts relative to each other) rather than the translational aspect (changes in the body location in space over time) of human movements (Masselink & Lappe, 2015). Scrambled biological motions were created by randomizing the starting positions of each point while keeping its motion path within the area covered by the Figure 1.…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
“…Recent research has revealed that humans are sensitive to the temporal binding between limb movements and body displacements, given that we commonly observe the two types of motion occurring in near synchrony. Disrupting the temporal congruency between the two sources of motion information curtails the perception of animacy (Thurman & Lu, 2013), the detection of social interaction between two agents (Thurman & Lu, 2014), and the discrimination of locomotion style (Masselink & Lappe, 2015;. However, it is unclear whether people show tolerance to some situations in which limb movements and body displacements are temporally misaligned but in a causally consistent way (e.g., limb movements may be shifted ahead in time but still precede body displacements in locomotion).…”
Section: Research Articlementioning
confidence: 99%
“…It is characterized by an articulation and a translation component. Articulation refers to the relative change of the joint positions to each other ( Blake & Shiffrar, 2007 ; Johansson, 1973 ; Masselink & Lappe, 2015 ). Translation refers to the linear progressive motion of the body through space ( Blake & Shiffrar, 2007 ; Masselink & Lappe, 2015 ; Riddell & Lappe, 2018 ).…”
Section: Introductionmentioning
confidence: 99%